COLLOCATION OF ISOLATION IN THE CORPUS OF ENGLISH WEB 2018 AND COVID 19: SEMANTIC APPROACH - Rabiyatul Adawiyah, Siti Lutfiah; Firdausi, Annisa Nurul (Journal of Language, Literature and Teaching, 2023)
When studying language, it is not only limited to studying the meaning of the word for word but also how one-word collocates with another word. This study was conducted to know the differences in collocations from the word isolation since the beginning of covid 19. This study used a corpus-based approach and qualitative research methods. The research data was collected from two different corpora, the English Web 2018 and Covid 19. Six collocations were taken from each corpus with the highest MI value. The results show differences in collocations in the word isolation since the emergence of Covid 19. In corpus English Web 2018, one collocation shows a negative meaning and four collocations indicate positive meanings. While in the covid 19 corpus, two collocations show a negative meaning, and three collocations show a positive meaning.